Economic Education In Preschool And Primary School Age" - Kasimova Mohigulkhon (Peerian Journals Publishing, 2024)
The article highlights the problems of economic education in preschool and school age. The meaning and features are revealed, as well as examples and methods of economic education of children of preschool and school age.
Keywords: Economic; upbringing; children; formation